Benefits and risks of structuring and/or coding the presenting patient history in the electronic health record: systematic review. Issue 4 (10th February 2012) - Fernando, Bernard; Kalra, Dipak; Morrison, Zoe; Byrne, Emma; Sheikh, Aziz
Abstract : Background: Patient histories in electronic health records currently exist mainly in free text format thereby limiting the possibility that decision support technology may contribute to the accuracy and timeliness of clinical diagnoses. Structuring and/or coding make patient histories potentially computable. Methods: A systematic review was undertaken of the benefits and risks of structuring and/or coding patient history by searching nine international databases for published and unpublished studies over the period 1990–2010. The focus was on the current patient history, defined as information reported by a patient or the patient's caregiver about the patient's present health situation and health status. Findings were synthesised through a theoretically based textural analysis. Findings: Of the 9207 potentially eligible papers identified, 10 studies satisfied the eligibility criteria. There was evidence of a modest number of benefits associated with structuring the current patient history, including obtaining more complete clinical histories, improved accuracy of patient self-documented histories, and better associated decision-making by professionals. However, no studies demonstrated any resulting improvements in patient care or outcomes. When more detailed records were obtained through the use of a structured format no attempt was made to confirm if this additional information was clinically useful. No studies investigated possible risks associated with structuring the patient history. No studies examined coding of the patient history. Conclusions: There is an insufficient evidence base for sound policy making on the benefits and risks of structuring and/or coding patient history. The authors suggest this field of enquiry warrants further investigation given the interest in use of decision support technology to aid diagnoses.